A novel recessive truncating mutation in MYO15A causing prelingual sensorineural hearing loss. (February 2016) - Li, Wei; Guo, Luo; Li, Yu; Wu, Qianru; Li, Qingzhong; Li, Huawei; Dai, Chunfu
Abstract: Hearing loss (HL) is one of the most common human defects which affects millions of people globally. The identification of deafness-related genes or loci may facilitate basic and clinical translational research on this disorder. Here, we investigated a Chinese family with autosomal recessive non-syndromic hearing impairment. Using targeted massively parallel sequencing, we identified a novel homozygous mutation, c.3525_3526insA and p.Q1175fsX1188 (NM_016239), in exon 2 of MYO15A . Sanger sequencing confirmed that affected siblings were homozygous for the mutation, whereas both normal hearing parents were heterozygous. The mutation was absent in 96 healthy controls and public databases. The insertion leads to a frameshift and a truncated form of the protein, resulting in the pathogenic effect of hearing loss for the patients. Mutations in exon 2 of MYO15A may cause a less severe phenotype, facilitating the rapid identification of mutations in exon 2 among the 66 exons when linkage of less severe hearing loss to Deafness, Autosomal Recessive 3 (DFNB3) is detected. Our data provide additional molecular information for establishing a better genotype–phenotype understanding of DFNB3.